2023
DOI: 10.1039/d2ob01956f
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-catalysed hydroaminoalkylation of on-DNA N-arylamines

Abstract: An efficient approach to the photoredox-catalysed hydroaminoalkylation between on-DNA secondary N-substituted (hetero)arylamines and vinylarenes has been developed and explored. The methodology was examined with a broad scope of vinylarenes and...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Given that the chemical space and structural diversity of DEL are pivotal in the binder selection process, considerable efforts have been directed toward constructing diverse libraries, each emphasizing a specific structural motif. However, such existing libraries remain confined to pharmacologically relevant chemical spaces, constrained by library design .…”
mentioning
confidence: 99%
“…Given that the chemical space and structural diversity of DEL are pivotal in the binder selection process, considerable efforts have been directed toward constructing diverse libraries, each emphasizing a specific structural motif. However, such existing libraries remain confined to pharmacologically relevant chemical spaces, constrained by library design .…”
mentioning
confidence: 99%
“…[6c,8] Consequently, there is continued interest in expanding the scope of DNA-compatible chemical reactions. [4b,9] Towards this goal, recent successes in multicomponent, [10] photocatalysis, [11] cycloaddition [12] and sp 2 -sp 3 crosscoupling [13] reactions on DNA, among others [9] have created new opportunities for DEL synthesis. For example, researchers at Pfizer have demonstrated that C(sp 3 )À H activation can be realized on DNA to merge small rings with heterocycles (Figure 1C).…”
mentioning
confidence: 99%